Success buill to last menciptakan hidup yang berarti / Jerry Porras, Stewart Emery, Mark Thompson ; editor Audina Furi Nirukti , Daniel P.Purba - PORRAS, Jerry; Emery, Stewart; Thompson, Mark; Nirukti, Audina Furi; Purba, Daniel P. (2009)
XV,340 hlm 19 cm